The Creation and Research of Installation Art Containing the Cultural Connotation of Confucius’ Benevolence - Han, Chao; CHAIYAKUT, PONGDEJ; PANTHUPAKORN, PORADEE (Chinese Language and Culture Journal, 2025)
Confucius's benevolence not only occupies an important position in ancient ethics, but also has far-reaching significance for the moral practice of modern society. This study explores the integration of Confucian "benevolence" philosophy and installation art, and then creates an art installation that can convey Confucius' benevolence and promote its positive impact on modern society. The installation work design creates a quiet space with a three-layer gauze curtain structure. Through the interweaving of light and shadow and the quiet atmosphere, it guides the audience into a state of meditation and introspection. The three reflective questions raised in the work: "Do you care about others?", "Do you restrain yourself and abide by legal ethics?", "Do you forgive others?". It not only promotes personal reflection on the core values ​​of benevolence, but also calls on modern society to maintain the virtues of caring for others, abiding by social norms and forgiving others in a fast-paced life. The combination of Confucius' benevolence and installation art not only expands the form and depth of cultural experience, but also provides a new method for the inheritance and innovation of Confucius' thoughts in modern society.